THE MAIN CHARACTER’S DEPRESSION IN JASMINE WARGA’S MY HEART AND OTHER BLACK HOLES - Mary Roselina Vernanda Rotty; Ismiati (Conscientia, 2021)
This research aims to discuss the depression of the main character in Jasmine Warga’s My Heart and Other Black Holes. Depression has usually been too late to realize.  When the depression comes to a suicide, people finally notice there is a case called depression. The research are to find out the symptoms of the depression that leads to a suicide attempt and the factors that help to overcome the depression.  The descriptive qualitative method with a psychological approach is applied. The symptoms of depression found in the main character are: believing no one cares, loss of hope, living in the past, and self-centeredness. The factors that influence the main character Aysel to overcome her depression and canceling the suicide are her family, her partner Roman and Roman’s mother. At the end, the main character, Aysel, is able to overcome her depression and decides to make a new better life.